Real-time pricing for aggregates energy resources in the Italian energy market. (1st July 2015) - Favuzza, S.; Galioto, G.; Ippolito, M.G.; Massaro, F.; Milazzo, F.; Pecoraro, G.; Riva Sanseverino, E.; Telaretti, E.
Abstract: Over the last decade, the architecture of the energy market has radically changed. In many countries end-users are now able to directly access the market, which has given rise to the question of how they can actively participate in that market. End-users can comprise a critical mass through aggregation that is carried out by a third party – to wit the "loads aggregator." This paper proposes a new framework for generating feasible real-time price curves for those end-users in a demand-response management process. The underlying algorithm generates output curves as the solution to a constrained optimization problem whose objective function is the aggregator's economic benefit. A case simulation study of the Italian market, with various parameter options, illustrates the procedure. Highlights: Management of customer storage systems in presence of dynamic electricity prices. The strategy exploits a load-shifting operation ensuring a profit for the end-user. The algorithm gives curves as solution of a constrained optimization problem. The objective function maximizes the economic benefit of aggregator and end users.